2023
DOI: 10.3390/ijms24032352
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photobiomodulation of the Peripheral Nerve Inhibits the Neuronal Firing in a Rat Spinal Dorsal Horn Evoked by Mechanical Stimulation

Abstract: Photobiomodulation has analgesic effects via inhibition of nerve activity, but few reports have examined the effects on the spinal dorsal horn, the entry point for nociceptive information in the central nervous system. In this study, we evaluated the effects of laser irradiation of peripheral nerve axons, which are conduction pathways for nociceptive stimuli, on the neuronal firing in lamina II of the spinal dorsal horn of a rat evoked by mechanical stimulation with von Frey filaments (vFF). In order to record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…We attempted to compare the effects of direct laser irradiation on the sciatic nerve using the same experimental setup in the past [23] with the effects of percutaneous irradiation in this study. The vFF-evoked firing frequency of the neurons varied widely, and it was difficult to compare the firing frequency values.…”
Section: Comparison Of the Effects Of Percutaneous Pbm And Direct Pbm...mentioning
confidence: 99%
See 4 more Smart Citations
“…We attempted to compare the effects of direct laser irradiation on the sciatic nerve using the same experimental setup in the past [23] with the effects of percutaneous irradiation in this study. The vFF-evoked firing frequency of the neurons varied widely, and it was difficult to compare the firing frequency values.…”
Section: Comparison Of the Effects Of Percutaneous Pbm And Direct Pbm...mentioning
confidence: 99%
“…This study suggested that laser irradiation inhibited the activity of Aδ and/or C fibers [23] because Aδ and C fibers innervate lamina II [30]. However, because the sciatic nerve was exposed and the laser was applied directly [23], it is unknown whether percutaneous irradiation, used in clinical practice, also inhibits neuronal firing in the lamina II of the spinal dorsal horn.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations